Сумісна дія фітодобавок та селеніту натрію на продуктивність курей-несучок та якість продукції за техногенного навантаження - Антоненко, Петро Павлович; Antonenko, Petro; Antonenko, P. P.; Ковальова, Ірина Володимирівна; Kovalova, Іrina (Білоцерківський національний аграр. ун-т., 2016)
Наведені дані щодо впливу кормових фітодобавок Фітопанк, Фітохол та селеніту натрію в період інтенсивної яйцекладки курей-несучок за умов техногенного навантаження. Встановлено збільшення продуктивності курей-несучок від 9,3 до 9,9 %, маси яєць від 1,9 до 2,5 %. За 6 місяців експерименту різниця між кількістю знесених яєць на середню несучку в дослідних групах, порівняно з контрольною, становила від 12,7 до 13,5 шт. Середня маса яєць птиці дослідних груп збільшилась на 3,7–4,0 %, жовтка яєць – на 2,8–7,4 %, яєчної шкаралупи – на 5,4 – 7,8 %, індекс форми яєць – на 0,8–1,2 %. Предзабійна маса курей-несучок підвищилась від 8,0 до 8,8 % і відповідно збільшилася маса непатраних тушок від 18,5 до 20,3 %, а також маса напівпатраних тушок від 17,0 до 21,5 % та патраних тушок – від 17,9 до 20,4 %. The aim was to investigate the effect of sodium selenite combined with dietary herbal supplements Phytopank and Phytohol on productivity of laying hens in man-made environment loaded with heavy metal compounds. The study was conducted on laying hens "Adler silver" breed in terms of the private farm of "TAHR" Odessa region, Bilyaivka area. According to the principle-group counterparts, there were formed four groups: one – control and three experimental (60 heads in each). Feeding and keeping terms for all groups of laying hens met all the veterinary and sanitary standards. Birds from control and experimental groups were kept in the cages. Density of birds was according to existing rules. Feeding of birds was conducted with a full mixed fodder. Laying hens from the first research group in addition to the basic diet received selenium at a dose of 0.2 mg/kg of dry matter of mixed fodder. As a source of selenium, sodium selenite was used (TU-6-09-1315-76), with a conversion factor element in salt 2.2. Supplement was thoroughly mixed with mixed fodder. Mixed fodder was fed under the existing rules. Laying hens from the second experimental group were fed a full mixed fodder and were watered herbal Phytopank, Phytohol. Analysis of the research indicates that including of sodium selenite in the diet of laying hens from the first experimental group eggs mass index at the end of the study increased by 1.9 % compared with the control group. In laying hens from the second experimental group an increase in egg weight was also observed compared with the control group by 2.3 %. A similar situation was observed in laying hens from the third research group. The difference was 2.5 % (p<0.001). It should be noted that with the increase of egg mass the mass of its parts increases. So, the average weight of egg yolk of laying hens from the first experimental group fed with sodium selenite increased by 2.8 %. In laying hens from the second experimental group given herbal dietary supplement an increase in the average weight of the yolk by 7.4 % (p<0.001) was also observed. In the third experimental group, administered in the diet sodium selenite combined with herbal dietary supplement the average yolk mass increased by 7.0 % compared to the control group. Eggs quality directly depends on egg weight and the thickness of the shell and its mass. As it was seen from the results eggshell mass index increased at the end of the experiment in laying hens from the first experimental group by 7.8 % (p<0.05) compared with control. In laying hens from the second experimental group given herbal dietary supplement an increase in egg shell weight by 5.4 % at the end of the experiment was also observed A similar trend of increasing egg shell weight by 6.2 % was observed in laying hens from the third experimental group fed with sodium selenite in combination with medicines. In laying hens as from the second experimental group given herbal dietary supplement with basic diet and from the third experimental group fed with sodium selenite combined with herbal dietary supplement index indicator of eggs form was significantly higher compared with the control group, and was 77.0 % respectively. In laying hens from the first experimental group where diet was administered with sodium selenite significant differences from the control group on this indicator were not observed. When studied the average weight of egg white and thickness of egg shell significant difference among the research and control groups of hens was not observed. Analyzing the results we can conclude that during the experiment an increase in productivity in all research groups was observed compared to the control. Thus, in the first experimental group, which was administered in the diet sodium selenite, egg production increased by 9.5 % in laying hens from the second experimental group in the application of herbal dietary supplement an increase – 9.3 % in the third experimental group, in terms of the combined sodium selenite with herbal dietary supplement productivity increased by 9.9% compared with the control group at the end of the experiment. The results of research proved that complex use of herbal dietary supplements Phytopank and Phytohol and sodium selenite for laying hens during active egg laying period has positive impact on the morphological characteristics of eggs, this is confirmed by increasing their mass to 2.5 % (p<0.001) yolk to 7.4 % (p<0.001) and egg shell to 7.8 % (p<0.001). Egg production increased by 9.9 %. Also complex use in the diet of laying hens, sodium selenite and herbal dietary supplements Phytopank and Phytohol has significant impact at ant on slaughter weight. Prospects for further research are explored in action of herbal dietary supplement and sodium selenite on protein metabolism during intensive productivity of laying hens.
Complex action of dietary herbal supplement and sodium selenite on productivity of laying hens and products quality at technogenic loading
Keywords: несучість; egg production; тушка; carcass; важкі метали; heavy metals; кури-несучки; laying hens; селеніт натрію; sodium selenite; Фітопанк; Phytopank; Фітохол; Phytohol